Reflections on the Formation of a Child’s Mathematical Culture at the Beginning of School Maturity - Makiewicz, Małgorzata; Michalak, Konrad (Journal of Education, Technology and Computer Science, 2021)
The authors of the article discuss the issue of mathematical culture concerning the education of the youngest participants of the educational system – children, in the course of preschool and school education in grades 1–3. The authors also refer to the problem of developing the mathematical culture of the school pupil, in the perspective of the transformation of the Polish educational system, challenges connected with modern education and its transformation on the national area.